Pengaruh Durasi Pengobatan dan Preferensi Pasien Kanker Stadium Akhir terhadap Layanan Homecare di Rumah Sakit Medistra pada Tahun 2021-2023 - Putra, Peter Brian Sutanto, Dr; Suwangto, Erfen Gustiawan, Dr; Djuartina, Tena, Dr; Budianto, Iskandar Rahardjo, Dr; Lesmana, C. Rinaldi A. (Jurnal Penyakit Dalam Indonesia, 2024)
Introduction. Cancer is still an enormous health problem in the world and rank second as the most common cause of mortality. End-stage cancer requires end-of-life or palliative care to improve the patient’s quality of life before death. Homecare services have become an option for providing palliative care to avoid long-term hospital stays. The study aimed to provide an overview of the treatment duration and other factors in end-stage cancer patients regarding the selection of homecare services at Medistra Hospital during the period of 2021-2023. Methods. This study with a cross-sectional design analyzed medical records of end-stage cancer patients who received palliative homecare services at Medistra Hospital from 2021 to 2023. Chi-square analysis was used to describe the association between gender, treatment duration, and cancer type with the decision to choose homecare services. The Mann-Whitney test was conducted to describe the relationship between age and the decision to choose homecare. Results. Out of 595 end-stage cancer patients, 429 chose to undergo palliative homecare. Males represented the majority in both the homecare group (53.1%) and the non-homecare group (56.6%). Patients who chose homecare were generally older (median age 65 years) compared to those who did not (median age 61 years, p = 0.002). Hematologic cancers were most common in the non-homecare group (25.3%), while gastrointestinal cancers were the most prevalent in the homecare group (39.9%). Patients with a treatment duration of less than 8 weeks from diagnosis were more likely to choose homecare, while those with a duration of 8 weeks or more were more likely to decline homecare (98.6% vs. 3.6%, p <0.001). Conclusion. Treatment duration and age are significant factors that related to the decision of end-stage cancer patients to choose homecare services.